Astrocyte‐specific insulin‐like growth factor‐1 gene transfer in aging female rats improves stroke outcomes. Issue 7 (20th March 2017) - Okoreeh, Andre K.; Bake, Shameena; Sohrabji, Farida
Abstract: Middle aged female rats sustain larger stroke infarction and disability than younger female rats. This older group also shows age‐related reduction of insulin like growth factor (IGF)−1 in serum and in astrocytes, a cell type necessary for poststroke recovery. To determine the impact of astrocytic IGF‐1 for ischemic stroke, these studies tested the hypothesis that gene transfer of IGF‐1 to astrocytes will improve stroke outcomes in middle aged female rats. Middle aged (10‐12 month old), acyclic female rats were injected with recombinant adeno‐associated virus serotype 5 (AAV5) packaged with the coding sequence of the human (h)IGF‐1 gene downstream of an astrocyte‐specific promoter glial fibrillary acidic protein (GFAP) (AAV5‐GFP‐hIGF‐1) into the striatum and cortex. The AAV5‐control consisted of an identical shuttle vector construct without the hIGF‐1 gene (AAV5‐GFAP‐control). Six to eight weeks later, animals underwent transient (90 min) middle cerebral artery occlusion via intraluminal suture. While infarct volume was not altered, AAV5‐GFAP‐hIGF‐1 treatment significantly improved blood pressure and neurological score in the early acute phase of stroke (2 days) and sensory‐motor performance at both the early and late (5 days) acute phase of stroke. AAV5‐GFAP‐hIGF‐1 treatment also reduced circulating serum levels of GFAP, a biomarker for blood brain barrier permeability. Flow cytometry analysis of immune cells in the brain at 24 hr poststroke showed that AAV5‐GFAP‐hIGF‐1 altered the type of immune cells trafficked to the ischemic hemisphere, promoting an anti‐inflammatory profile. Collectively, these studies show that targeted enhancement of IGF‐1 in astrocytes of middle‐aged females improves stroke‐induced behavioral impairment and neuroinflammation. Main Points: Ischemia‐induced damage and disability is worse in middle‐aged female rats than young female rats. Astrocyte‐specific gene transfer of IGF‐1 improves the immunological response and motor sensory recovery after stroke in middle‐aged females.